Different Types of Multi Class Classification Algorithms: A Study - Johnsymol, Joy; Krishnan, Rakhi; Nazeer, Ziyad (International Journal of Computer Sciences and Engineering, 2021)
Classification is a crucial aspect of machine learning. Multi class Classification has an important role in the classification. It is an on-going research in machine leaning field. In this paper we will come to know about multi class classification algorithms. We will see different algorithms like Decision Tree, SVM, Random Forest, Naive Bayes etc. This is clear cut representation of the basic advantages and limitations regarding different types of classification algorithms and the various measures for implementing results. Nowadays, these types of algorithms are playing a substantial role among different program sequences so as to improve the quality of classification.